THE EFFECT OF STRENGTHENING EXERCISE ON THE QUADRICEPT AND HAMSTRING MUSCLES ON CHANGING FUNCTIONAL KNEES FOR PATIENTS WITH KNEE OSTEOARTHRITIS - Sulfandi Sulfandi; Nety Eka Jayanti; Arisandy Achmad; Kasim Nurhas Jaiddin; Furkan Furkan (Journal Physical Education, Health and Recreation, 2022)
Introduction Osteoarthritis is a failure to repair damage in the joints caused by excessive mechanical stress. This disease is chronic, degenerative, non-inflammatory, and slowly progressive, one of which is characterized by decreased function. Osteoarthritis is a form of osteoarthritis that affects people in old age or adulthood. The cause of osteoarthritis is not known with certainty, but age, gender, race, genetics, obesity, and physical activity are risk factors that lead to pathological changes and affect the decreased functional ability. This decrease in functional ability in osteoarthritis can be overcome by isometric exercise.Methods: The research design used was a pre-experimental design with an approach of pretest-posttest one group design. The sampling technique used was total sampling, with a total of 20 respondents aged 40–70 years. Exercise with a frequency of 2 times a week for 8 weeks at an intensity of 3 repetitions for 15 minutes. The measuring instrument in this study used WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index). Normality test using the Shapiro-Wilk test, hypothesis testing using the Wilcoxon Test.The results showed the level of functional ability before being given the intervention had an average value of 2.30 and after being given the intervention had an average value of 1.40. Statistical test results showed p-value = 0.000 (p 0.005). This shows that there is an effect of isometric exercise on changes in functional abilities of patients with Samarinda knee osteoarthritis at AW Sjahranie Hospital.Conclusion: Giving isometric exercise to the quadriceps and hamstrings has an effect on improving the functional ability of the knee in patients with osteoarthritis.